Fried! : when lightning strikes - Barnham, Kay. (Mankato, Minn. : Capstone Press, 2008)
Presents the science of lightning and thunderstorms, including dangers and safety precautions.
Splitting the sky -- Monster sparks -- Thunderbolts and lightning -- Very, very frightening -- Down to earth -- Weird lightning -- Bull's-eye! -- Under attack -- Zap, crackle, and pop -- Full metal jacket -- View from space -- Dust demons -- Liftoff! -- Glossary.
Includes bibliographical references (p. 31) and index.
5.1
3-6
Keywords: Lightning -- Juvenile literature; Thunderstorms -- Juvenile literature; Lightning; Thunderstorms; Lightning; Thunderstorms